El exilio en Adieu, vive clarté... de Jorge Semprún: la superación de un trauma - Rodríguez, Rita (Anales de Filología Francesa, 2018)
Exile is an experience with traumatic consecuences that has accompanied the human being during all the History. Traumatism is characterized by the multiplicity and diversity of manifestations, it produces an indelible split in life. In literary fields, it appears as the motive of writing where the author seeks to understand and to give sense to the experience through writing. This article wants to analyze the experience of the exile of the writer Jorge Semprún. And that’s the reason why we first of all talk about the triple loss of his mother, his infancy and his home country; secondly, the compulsory adulthood will be exposed, and the end, the way he chose to take, will be analyzed. It helped him to overcome the consecuences of the exile and characterizes what he had to fight for during his life.